Эволюция театральных трактовок пьесы А. П. Чехова "Дядя Ваня" (1899 г.- кон.XX - нач. XXI ст.) - Нечипоренко, В.С (Культура народов Причерноморья, 2013)
В статье проанализированы театральные постановки пьесы А. П. Чехова «Дядя Ваня» на сцене Крымского академического русского драматического театра им. М. Горького, в период от 60-х гг. ХХ в. до начала ХХІ в. Ключевые слова: театр, драма, пьеса, Чехов, «Дядя Ваня». В статті проаналізовані театральні постановки п'єси А. П. Чехова «Дядя Ваня» на сцені Кримського академічного російського драматичного театру ім. М. Горького, в період від 60-х рр. ХХ ст. до початку ХХІ ст. Ключові слова: театр, драма, п'єса, Чехов, «Дядя Ваня». The article deals with the problems of Chekhov's plays for professionals in the field of drama, art and history of the theater, as well as all those interested in the fate of Chekhov's creativity. The interest of modern theaters to Chekhov's drama is due vitally relevant themes of his plays. Chekhov reflects on the man, his personality, thoughts, feelings, qualities, for his soul. The paper analyzes the theatrical plays of Anton Chekhov's "Uncle Vanya" at the stage of Gorky Crimean Academic Russian Drama Theater during the 60's of twentieth century and the beginning of XXI century. As a starting point of analysis was taken the first staging of the play "Uncle Vanya" had been exercised by Stanislavsky at Moscow Art Theatre. The study is selected Crimean theatrical culture, in particular M. Gorky Crimean Academic Russian Drama Theatre. A significant part of the work is characteristic productions of Chekhov's plays in an era directed by A. Novikov. The study addressed the problem of classical interpretation of the play "Uncle Vanya" for a hundred years and the author used the method of comparative analysis. Key words: theater, drama, play, Chechov, «Uncle Vanya».